The Impact of Place Identity in shaping the Design Idea- Analytical Study of the Architectural Students Products – Duhok University - Sadiq, Cebar J.; Khalil, Kadhim F. (Sulaimani Journal for Engineering Sciences, 2019)
Place identity is an architectural concept that cannot be ignored in the architectural culture of the Kurdistan region of Iraq, where it represents the image of the ego in the direction of architectural Specificity. The study is based on the impact of this concept on the shaping of design idea in architectural education, Whereas the previous theories that have been considered this concept provide a fragmented description, The research problem identified by the knowledge deficit on the impact of place identity factors in shaping the design idea of the products of architectural students, Through the methodology of the study we were able to identify the basic variables that constitute the place identity in both intellectual and physical ways and how to measure its impact in formulate the design idea for students, To the conclusion that the reflection of the intellectual aspect of place identity is proportional to the general cognitive perception of students (as the stages Progress) at the expense of physical aspects.
Keywords: Place identity; Place factors; Design idea; Architectural Students